Dissecting meningococcal disease and carriage traits using high throughput phenotypic testing. Issue 5 (27th May 2022) - Farzand, Robeena; Mourkas, Evangelos; Ste Croix, Megan De; Dave, Neelam; Jama, Abdullahi; Oldfield, Neil; Lucidarme, Jay; Turner, David; Borrow, Ray; Martinez-Pomares, Luisa; Sheppard, Samuel; Bayliss, Christopher
Abstract : Despite on-going vaccination programmes, Neisseria meningitidisis a majorcause of septicaemia and meningitis. In 2017-18, the MenW and MenY capsular groups caused 38% of all UK invasive meningococcal disease cases. Current policy is to generate genome sequences of all meningococcal disease isolates. Using this resource, we aim to determine how genetic variation contributes to phenotypic differences between carriage and disease isolates. We have adapted assays, mimicking carriage and disease behaviours, for high-throughput phenotypic testing of 335 MenW cc11 and MenY cc23 isolates. We are currently testing MenW cc11 disease and carriage isolates for cytotoxicity in a human lung epithelial cell line, growth in media and biofilm formation. Phenotypic differences are utilised as inputs for Genome Wide Association Studies enabling linkage of specific genomic variants, or variant combinations, with phenotypic variation. Genomic data include whole genome sequences and repeat-mediated phase variation states. The MenW cc11 isolates span two known phylogenetic clusters, original and 2013. Our preliminary data from high-throughput growth and biofilm assays showed no significant differences between these groups or sources (disease versus carriage); however, variations were observed within groups with, for example, distinctive cytotoxicity or biofilm differences between isolates. These variations may reflect physiological divergence due to minor genetic modifications between highly phylogenetically-related strains. Our assay systems are robust, reproducible, and easily scalable for efficient high-throughput genotypic and phenotypic testing. Thus, large-scale screening of phenotypic variation for infectious diseases is achievable and harnessable for cost-effective, direct evolutionary and epidemiological studies.